Measuring the impact introducing NHS 111 online had on the NHS 111 telephone service and the wider NHS urgent care system: an observational study - Richard M Jacques; Rebecca M Simpson; Tony Stone; Janette Turner; Jon Nicholl (BMJ Open)
Objectives To explore what impact introducing the National Health Service (NHS) 111 online service had on the number of phone calls to the NHS 111 telephone service and the NHS urgent care system.Design Observational study using a dose–response interrupted time series model and random-effects meta- analysis to estimate the average effect.Setting and participants NHS 111 telephone and online contacts for 18 NHS 111 area codes in England. NHS 111 telephone and online contacts data were collected between October 2010 to December 2019 and January 2018 to December 2019, respectively.Primary and secondary outcome measures Primary outcome: the number of triaged calls to the NHS 111 telephone service following the introduction of NHS 111 online. Secondary outcomes: total calls to the NHS 111 telephone service, total number of emergency ambulance referrals or advice to contact 999, total number of advice to attend an emergency department or other urgent care treatment facility, and total number of advice to contact primary care.Results For triaged calls, the overall incidence rate ratio (IRR) per 1000 online contacts was 1.013 (95% CI: 0.996 to 1.029, p=0.127). For total calls, the overall IRR per 1000 online contacts was 1.008 (95% CI: 0.992 to 1.025, p=0.313). For emergency ambulance referrals or advice to contact 999, the overall IRR per 1000 online contacts was 1.067 (95% CI: 1.035 to 1.100, p<0.001). For advice to attend an emergency department or other urgent care treatment facility, the overall IRR per 1000 online contacts is 1.050 (95% CI: 1.010 to 1.092, p=0.014). And finally, for those advised to contact primary care, the overall IRR per 1000 online contacts is 1.051 (95% CI: 1.027 to 1.076, p<0.001).Conclusions It was found that the NHS 111 online service has little impact on the number of triaged and total calls, suggesting that the workload for the NHS 111 telephone service has not increased or decreased as a result of introducing NHS 111 online. However, there was evidence to suggest an increase in the overall number of disposition recommendations (ambulance, emergency department and primary care) for NHS 111 telephone and online services combined following the introduction of the NHS 111 online service.